Political corruption, trust, and household stock market participation - Bu, Di; Hanspal, Tobin; Liao, Yin (Journal of Banking & Finance, 2022)
We study how political corruption affects stock market participation among households in China. Our identification strategy exploits recent anticorruption campaigns that reduce households’ exposure to political corruption and within-province variation in lifetime exposure to local corruption. We find that households with higher corruption exposure participate less in the stock market at both the extensive and intensive margins. Removals of top provincial officials during the anticorruption campaign increase the probability of stock market participation by 3 percentage points and households’ net equity purchases and equity share percentage by 13.2 and 0.2 percentage points, respectively. The effect is predominantly driven by the nonpecuniary effect of corruption on households’ trust and perceptions of institutional quality rather than on households’ accumulation of wealth. Our work highlights the negative externalities of political corruption on financial markets.